2011
DOI: 10.3109/15622975.2011.591824
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-temporal disconnectivity and symptom severity in children with autism spectrum disorder

Abstract: Our findings support the hypothesis of abnormal white matter microstructure of fronto-temporal cortical networks in ASD, which are associated with core symptoms of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
72
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 50 publications
14
72
0
1
Order By: Relevance
“…This reduction in FA is in line with the findings of several previous studies in ASD ( Jeong et al, 2011;Jou et al, 2011aJou et al, , 2011bNoriuchi et al, 2010;Poustka et al, 2012;Shukla et al, 2011). Increased RD in the same tract in autism was also reported in a few previous studies ( Jeong et al, 2011;Shukla et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This reduction in FA is in line with the findings of several previous studies in ASD ( Jeong et al, 2011;Jou et al, 2011aJou et al, , 2011bNoriuchi et al, 2010;Poustka et al, 2012;Shukla et al, 2011). Increased RD in the same tract in autism was also reported in a few previous studies ( Jeong et al, 2011;Shukla et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…For example, reduced FA in ASD participants has been linked to increased ASD symptom severity and behaviors (Catani et al, 2008;Noriuchi et al, 2010;Poustka et al, 2012;Thakkar et al, 2008), as well as performance intellectual quotient (PIQ) (Alexander et al, 2007;Lange et al, 2010;Lee et al, 2009). In addition, alterations in FA in participants with ASD have been related to language abilities (Fletcher et al, 2010;Li et al, 2014;Mills et al, 2013), executive functions (Nair et al, 2015), and motor performance (Thompson et al, 2016).…”
mentioning
confidence: 99%
“…Furthermore, we expected group status to moderate the association between abnormal white matter structure in the left uncinate and socio-affective deficits. In particular, we expected white matter structure in the left uncinate to be linked to socio-affective skills in individuals with ASD, but not in TD individuals, since brain behavior associations are more frequently identified in individuals with neuropsychiatric disorders when compared to neurotypicals (Baur et al, 2011;Poustka et al, 2012;Thomason and Thompson, 2011). To test specificity of group effects as well as moderating effects, we also analyzed group differences in the right uncinate fasciculus and tested moderation effects of group status on the association between white matter tissue structure in the uncinate fasciculi and another core feature of ASD, namely restricted and repetitive behaviors.…”
Section: The Current Studymentioning
confidence: 99%
“…It therefore connects basic emotion processing areas with regions involved in higher order processing, including emotion regulation. The uncinate has been linked to processing of emotional information in healthy populations (Frey et al, 2000), and has been reported to be related to impaired socio-emotional processing in disorders such as fronto-temporal dementia (Von der Heide et al, 2013), and also more generally with symptom severity in individuals with ASD (Poustka et al, 2012).…”
Section: Potential Neural Correlates Of Socio-affective Deficits In Amentioning
confidence: 99%
“…However, analyzing structural connectivity and betweenness centrality in the same data set, differences in neuroanatomical areas spread over the whole brain (uncinate fasciculus, superior longitudinal fasciculus, Wernicke's area) were revealed [28,47]. Many of these affected areas belong to the heteromodal association cortex (HASC), such as altered connectivity in frontal and parietal areas by the uncinate and the superior longitudinal fasciculus and altered betweenness centrality in Wernicke's area.…”
Section: Aims and Hypothesesmentioning
confidence: 96%